Amo letter manufacturing sdn bhd love letter biscuit - Mazalan, Nurul Fariha Aina; Mohd Ghazali, Nurul Aina; Dzahuren, Dzareenatasya; Saiful Amin, Nurul Aina; Izani, Nur Aliyaniyani (2021)
The company name is Amo Letter Manufacturing Sdn. Bhd. This creative name is proposed by our partnership members with a tagline ‘Made with Love’. We produce traditional wafer snacks, “Amo Letter” directly to our customer. We serve kuih kapit which is free from harmful food additives. Kuih kapit is a traditional Chinese New Year thin crispy crepe like biscuits. It is because the folding of the Kuih kapit itself is similar to writing and folding love letters and ready to be sent to our loved ones. Amo letter comes in a small box with different patterns and colors. It is also suitable as a gift for any occasion such as a wedding door gift. Amo Letter Manufacturing Sdn. Bhd is a business based on partnership which consists of five members. We choose partnership business because we find it easier to set up the business and manage any process related to the regulations. Each partner contributes RM 34 204.40 and the total equity contribution is RM171 022. Amo Letter Manufacturing will operate from Sunday to Thursday. We also offer delivery services starting from 11 a.m until 6 p.m. Our company is located at Lot 44/KL Taman Perindustrian Kecil dan Sederhana, Pasir Mas, Kelantan. The population here is 189 292 people. The location of the premises is very strategic because it is nearby our target market. Thus, it will be easier for the community to notify our business. Our target market is focusing on college students, private employees as well as digital customers. We use different flavors such as Cocoa Powder and Strawberry Pulp Powder as one of our strategies to produce good products. Light and dry texture of our products give us an opportunity to produce marketable products and services. In order to make it more attractive and special, we use modern packaging with different patterns and colors based on the flavor inside. In a nutshell, a business plan is a necessary tool for entrepreneurs. It is the main preparation for a group of people including owners, bankers, suppliers, customers and employees. This plan consists of marketing, operation, organization and financial plan. We believe we will be able to achieve our business goal together with a statement of financial position. We will get our return modal within the short time and current ratio will cover our liabilities and. Therefore, our business will grow even further in the future.